Uma contribuição da contabilidade na melhoria do processo das prestações de contas nas entidades do terceiro setor: estudo de caso: Fundação de Ensino Eurípides Soares da Rocha - UNIVEM - Souza, Marlene de Fatima Campos (2011)
The Third Sector institutions are considered agents responsible for the changing of society, and act as an instrument of the State in several areas, aiming at responding to social demands. To accomplish this task, it is fundamental that they have an adequate and efficient management that guarantees continuity and sustainability for these institutions. Regarding management, there are some essential obligations for the perfect operation of these institutions, such as the mandatory accountability to certification and regulation agencies, to social investors, and to society in general, with emphasis to the certification agencies, since certification provides contribution and tax exemption when all the requirements demanded by law are met. Thus, we see Accounting as an essential tool, since it contributes to an efficient management, and is necessary to the decision making and to the establishment of accountability processes, because it provides necessary information to confirm the gratuity required by law. Aiming at evaluating the contribution of Accounting to the improvement of the accountability processes in Third Sector institutions, a case study was accomplished in a nonprofit institution of College Education, the Fundação de Ensino Eurípides Soares da Rocha, in the city of Marília, São Paulo State, where the visits, interviews and data collecting necessary for the study were made. Considering the main point of the research, the results indicate that Accounting, when made in a segregated, precise, and transparent form, evidences and proves the applications of gratuity offered by the institutions in order to keep the certifications. It was possible to verify that the institution studied uses Accounting as a management tool and as a fundamental element in the process of accountability, allowing the evaluation of results of certification maintenance